STUDIES ON THE FOOD AND ALIMENTARY CANAL OF THE INDIAN MAJOR CARPS II. LABEO ROHITA (HAM.) AND III. CIRRHINA MRIGALA (HAM.) - Kamal, M Yusuf (Indian Journal of Fisheries, 2011)
THE present communication, dealing with the food consumed and the differentiation of the alimentary canal and associated structures in Labeo rohita and Cirrhina mrigala form the second and third parts in the series of studies on the food and alimentary canal of the Indian major carps. The usefulness of the study, details regarding the material that formed the basis of these investigations and the methods adopted for the study have been discussed in detail in the earlier paper (Kamal, 1967).